A cross-sectional exploratory study of food literacy among Saudi parents of adolescent children aged 10 to 19 years - Bookari, Khlood (Frontiers in Nutrition, 2023)
Abstract Parental food literacy is fundamental in laying a solid foundation for healthy eating among their children. This study aimed to (1) evaluate the current state of food literacy among Saudi parents of 10-19 years old adolescent children, and (2) determine the correlates associated with parental food literacy. This cross-sectional study was conducted between April and June 2022, with a convenience sample of 1845 Saudi parents (mean age= 45.1 ± 11; mothers: 56%). A Short Food Literacy Questionnaire (SFLQ) was used to meet the study aims. Findings showed that around 46% of parents had poor food literacy. Fathers were 2.4 times more likely than mothers to be food illiterate (OR=2.4, CI=1.9-3.0, p-0.001). Parents residing in Riyadh, Northern borders, Jawf, or Ha’il had a three times higher risk of being food illiterate than those residing in other provinces (OR=3.2, CI=2.6-3.9, p<0.001). Parental overweight or obesity increased their risk of being food illiterate by 60% (OR=1.6, CI=1.3-2.1, p<0.001). Healthy parents, in contrast to those having a chronic disease (s), had a 60 % higher probability of food illiteracy (OR=0.4, CI=0.3-0.6, p<0.001). Educated parents had a three times higher risk of being food illiterate (vs. uneducated parents, OR=3.0, CI=1.6-5.8, p=0.001). Parents making less than 3000 Saudi Riyal (SR) per month (<798 USD/779 EUR) were 40% more likely to be food illiterate than those who reported 3000-25000 SR (798-6652 USD/ 779-6499 EUR) (OR=0.6, CI=0.4-0.9, p=0.02), and 70% more likely to be food illiterate than those making more than 25000 SR (>6652 USD/6497 EUR) (OR=0.3, CI=0.2-0.6, p<0.001). Parents who lived in crowded households were twice as likely to be food illiterate as those who did not (OR=1.9, CI=1.5-2.4, p<0.001). The current study findings should be employed in future programming and policy-making approaches to reach Saudi parents for necessary food literacy interventions. These interventions could include bolstering their confidence while cooking, buying groceries, reading nutrition labels, and integrating them into nutrition education lessons with their children in school settings.